An antibacterial, moisture-proof and wear-resistant coating for air ducts and a preparation method thereof
Patent Information
- Application Number
- CN202611358488.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明的目的在于提供一种风管用抗菌防潮耐磨涂层及其制备方法,以解决上述背景技术提出的目前风管内部温湿适宜且含尘,易滋生微生物并形成生物膜,同时结露与高湿导致涂层失效、基材腐蚀,加之粉尘冲刷磨损,对风管防护提出了耐菌、防腐、耐冲蚀的综合要求的问题
[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: This antibacterial, moisture-proof, and wear-resistant coating for air ducts and its preparation method, through the synergistic design of the primer layer and the functional topcoat layer, combined with electrochemical protection, hydrophobic wear-resistant modification, and multiple antibacterial and anti-mildew mechanisms, improves the comprehensive protective performance and service life of the air duct coating in humid, dusty, and microbial contaminated environments. The specific details are as follows:
Smart Images

Figure CN122917636A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional protective coating materials technology, specifically to an antibacterial, moisture-proof, and wear-resistant coating for air ducts and its preparation method. Background Technology
[0002] With the rapid development of modern architecture, medicine, electronics, food processing and underground space, ventilation ducts (hereinafter referred to as "ducts") are the core components of building ventilation and air conditioning systems. The performance of their inner wall coating directly affects the system's operating efficiency, indoor air quality and duct lifespan. During long-term service, the inner wall of ducts is continuously subjected to the coupled effects of multiple factors such as high-speed airflow scouring, temperature and humidity changes, dust particle abrasion and microbial growth. Therefore, comprehensive performance requirements for protective coatings are put forward in multiple dimensions, including antibacterial, moisture-proof, wear-resistant and excellent adhesion.
[0003] As the core component of HVAC systems for transporting air, air ducts are constantly exposed to a relatively enclosed environment with suitable temperature and humidity and containing organic dust. This environment is prone to the growth of bacteria, mold, and other microorganisms, forming biofilms. This not only leads to the deterioration of indoor air quality and the generation of odors, but also accelerates the aging and failure of the coating. At the same time, condensation or high-humidity water films often appear on the inner and outer walls of air ducts under cooling conditions. Conventional organic coatings are prone to losing their protective properties due to water absorption, swelling, penetration corrosion, and hydrolytic degradation, and the metal substrate faces the risk of electrochemical corrosion. In addition, dust particles carried by the airflow continuously scour and wear the duct wall at bends, diameter changes, and other locations, and ordinary coatings are difficult to meet the requirements for long-term erosion resistance.
[0004] Therefore, an antibacterial, moisture-proof, and wear-resistant coating for air ducts and its preparation method are proposed to solve the problems mentioned above. Summary of the Invention
[0005] The purpose of this invention is to provide an antibacterial, moisture-proof, and wear-resistant coating for air ducts and its preparation method, in order to solve the problems mentioned in the background art, such as the suitable temperature and humidity inside air ducts, dust content, easy growth of microorganisms and formation of biofilms, condensation and high humidity leading to coating failure and substrate corrosion, and dust erosion, which put forward comprehensive requirements for air duct protection in terms of antibacterial, anti-corrosion, and erosion resistance.
[0006] To achieve the above objectives, the present invention provides the following technical solution: an antibacterial, moisture-proof, and wear-resistant coating for air ducts and its preparation method, comprising a primer layer and a functional topcoat layer sequentially disposed on the surface of the air duct substrate, wherein the primer layer is formed by mixing primer component A and primer component B and then coating and curing, wherein primer component A comprises, by weight, 15-20 parts of waterborne epoxy emulsion, 55-65 parts of zinc powder, 5-10 parts of phosphorus iron powder, 0.5-1 part of organic bentonite, 2-4 parts of co-solvent, and deionized water to make up to 100 parts;
[0007] The primer component B is a water-based epoxy curing agent, and its dosage is determined by calculating the equivalent of epoxy in primer component A and active hydrogen in primer component B.
[0008] The functional topcoat layer is formed by mixing and coating topcoat component A and topcoat component B, and then curing. Topcoat component A, by weight, comprises: 28-36 parts of waterborne epoxy emulsion, 12-18 parts of waterborne polyurethane dispersion, 2-4 parts of nano-α-Al₂O₃ surface-modified with silane coupling agent, 1-2 parts of polytetrafluoroethylene micropowder, 3-5 parts of sericite powder, 0.5-1.2 parts of silver-zinc-glass carrier inorganic antibacterial agent, and 0.5-1.2 parts of polyhexamethylene guanidine hydrochloride. 1.5 parts (based on a 20 wt% aqueous solution), 0.3-0.8 parts (based on a 10 wt% propylene glycol butyl ether solution), 0.3-0.8 parts hydrophobic fumed silica, 0.3-0.8 parts organobentonite, 2-4 parts film-forming aid, 0.1-0.3 parts defoamer, 0.1-0.3 parts leveling agent, 0.2-0.5 parts flash rust inhibitor, 0.2-0.5 parts thickener, and deionized water to bring the total to 100 parts;
[0009] The topcoat component B is composed of an aqueous epoxy curing agent and γ-glycidoxypropyltrimethoxysilane. The amount of γ-glycidoxypropyltrimethoxysilane is 1.5 to 2.5 wt% of the total mass of the topcoat component A. The amount of the aqueous epoxy curing agent is determined by calculation based on the equivalent of epoxy in the topcoat component A and the equivalent of active hydrogen in the topcoat component B.
[0010] The dry film thickness of the primer layer is 25–35 μm, the dry film thickness of the functional topcoat layer is 45–65 μm, and the total dry film thickness of the coating is 70–100 μm.
[0011] Preferably, in the functional topcoat layer, based on the total resin solids content of the aqueous epoxy emulsion and aqueous polyurethane dispersion in component A of the topcoat, the content of each component is as follows:
[0012] Nano α-Al₂O₃ 6~10wt%;
[0013] 2-4 wt% polytetrafluoroethylene micro powder;
[0014] 5-8 wt% sericite powder;
[0015] Silver-zinc-glass carrier inorganic antibacterial agent 1.0–2.0 wt%;
[0016] Polyhexamethylene guanidine hydrochloride, 0.3–0.8 wt% based on active ingredient;
[0017] Iodopropynyl butylcarbamate, 0.3-0.5 wt% based on active ingredient.
[0018] Preferably, the amount of waterborne epoxy curing agent in the primer B component and / or the topcoat B component is determined according to the ratio of epoxy equivalent in the primer A component or the topcoat A component to active hydrogen equivalent in the primer B component or the topcoat B component, which is 0.85 to 1.15; preferably 0.9 to 1.1; the γ-glycidoxypropyltrimethoxysilane in the topcoat B component is used as an interfacial coupling agent and a crosslinking promoter.
[0019] Preferably, the nano-α-Al2O3 modified with silane coupling agent has an average particle size of 50 nm and a specific surface area of ≥30 m² / g. The silane coupling agent used is γ-glycidoxypropyltrimethoxysilane, and its amount is 3 wt% of the mass of nano-α-Al2O3.
[0020] Preferably, the silver-zinc-glass carrier inorganic antibacterial agent has a silver content of 2-4 wt%, a zinc content of 10-20 wt%, a median particle size D50 ≤ 5 μm, and the carrier is borosilicate glass or zirconium phosphate; the polyhexamethylene guanidine hydrochloride has a molecular weight of 2000-5000 Da.
[0021] Preferably, the aqueous epoxy emulsion has an epoxy equivalent of 450–550 g / eq and a solid content of 50 ± 2%; the aqueous epoxy curing agent has an active hydrogen equivalent of 250–300 g / eq; and the aqueous polyurethane dispersion is an aliphatic polyester anionic dispersion with a solid content of 35 ± 2%, an elongation at break ≥ 300%, and a glass transition temperature of -30 to -20°C.
[0022] Preferably, the sericite powder has an aspect ratio ≥40; the polytetrafluoroethylene micro powder has an average particle size of 3-5 μm; and the zinc powder has a mesh size of 800 mesh and a zinc content ≥97 wt%.
[0023] This invention also discloses a method for preparing the aforementioned antibacterial, moisture-proof, and wear-resistant coating for air ducts, comprising the following steps:
[0024] Step 1, silane pretreatment of nano α-Al2O3: Nano α-Al2O3 is dispersed in anhydrous ethanol to form a suspension. After ultrasonic dispersion, γ-glycidoxypropyltrimethoxysilane is added, the pH is adjusted to 4-5, and the reaction is stirred at 50-70℃ for 2-6 hours. After separation, washing, drying and grinding, nano α-Al2O3 modified with silane coupling agent is obtained.
[0025] Step 2, Preparation of Topcoat Component A: Deionized water, organic bentonite, nano α-Al2O3 obtained in Step 1, polytetrafluoroethylene micro powder, sericite powder, silver-zinc-glass carrier inorganic antibacterial agent, and hydrophobic fumed silica are mixed, dispersed, and ground to a fineness ≤30μm to obtain a slurry; waterborne epoxy emulsion, waterborne polyurethane dispersion, polyhexamethylene guanidine hydrochloride aqueous solution, iodopropynyl butylcarbamate solution, film-forming aid, and anti-flash rust agent are added to the slurry and mixed evenly; then defoamer, leveling agent, and thickener are added to adjust the viscosity to 60-90s at Forck-4 cup, and the mixture is filtered to obtain topcoat component A;
[0026] Step 3, Preparation of primer component A: Mix and grind deionized water, organic bentonite, zinc powder and iron phosphate powder to a fineness of ≤30μm, then add water-based epoxy emulsion, cosolvent and defoamer and mix evenly, adjust the viscosity to 45-65s of Forecast cup 4, and filter to obtain primer component A;
[0027] Step 4, Coating and Curing: After degreasing, sanding, and silane pretreatment of the duct substrate, primer component A and primer component B are mixed and coated to form a wet film of 40-60 μm. The film is then pre-baked at 60-80℃ for 5-10 minutes until touch-dry to obtain a primer layer. Within 24 hours after the primer layer is surface-dry, topcoat component A and topcoat component B are mixed and coated to form a wet film of 80-120 μm. This film is then cured in stages to obtain the antibacterial, moisture-proof, and wear-resistant coating for the duct. The amount of water-based epoxy curing agent in primer component B and / or topcoat component B is determined according to the ratio of epoxy equivalent in primer component A or topcoat component A to active hydrogen equivalent in primer component B or topcoat component B, which is 0.85-1.15; preferably 0.9-1.1.
[0028] Preferably, the silane pretreatment in step four uses an ethanol / water solution with a mass concentration of 5 wt% γ-glycidoxypropyltrimethoxysilane, adjusts the pH to 4-5 with acetic acid, achieves a wet film thickness of 3-5 μm, dries at room temperature for 10-15 min, and completes the primer coating within 24 h.
[0029] Preferably, the step-curing process in step four is as follows: first, cure at 50-70°C for 20-40 minutes, then raise the temperature to 70-90°C and cure for 20-40 minutes, then allow to cool naturally and leave at room temperature for 24 hours to complete the curing.
[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: This antibacterial, moisture-proof, and wear-resistant coating for air ducts and its preparation method, through the synergistic design of the primer layer and the functional topcoat layer, combined with electrochemical protection, hydrophobic wear-resistant modification, and multiple antibacterial and anti-mildew mechanisms, improves the comprehensive protective performance and service life of the air duct coating in humid, dusty, and microbial contaminated environments. The specific details are as follows:
[0031] First, this invention constructs a two-layer coating structure of "primer layer + functional topcoat layer." Utilizing the synergistic effect of sacrificial anode protection and physical shielding provided by the high content of zinc powder and iron phosphorus powder in the primer layer, it can provide good electrochemical protection for the metal substrate of the duct in humid or condensing environments. The functional topcoat layer uses a composite film of waterborne epoxy emulsion and waterborne polyurethane dispersion, and incorporates nano-α-Al2O3 modified with a silane coupling agent, sericite powder, polytetrafluoroethylene micropowder, and hydrophobic fumed silica. This improves the coating's density and surface hydrophobicity, reduces moisture penetration and hygroscopic swelling, thereby improving the coating's moisture-proof and protective stability under high humidity conditions. Simultaneously, the excellent adhesion of the aforementioned wear-resistant components to the primer layer enhances the coating's erosion resistance and wear resistance under dusty airflow conditions, which helps extend the service life of the duct in complex operating environments.
[0032] Secondly, the functional topcoat layer incorporates a combination of silver-zinc-glass carrier inorganic antibacterial agents, polyhexamethylene guanidine hydrochloride, and iodopropynyl butylcarbamate, which inhibit the adhesion and reproduction of bacteria, molds, and other microorganisms on the coating surface through different mechanisms, reducing the risk of biofilm formation. The introduction of γ-glycidyl etheroxypropyltrimethoxysilane into the topcoat component B can participate in epoxy curing crosslinking and improve the organic-inorganic interface bonding, which helps to enhance the structural stability and comprehensive protective performance of the coating in humid environments, thereby reducing the problems of air quality deterioration and increased maintenance frequency caused by microbial contamination and coating aging. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the process flow structure of the present invention. Detailed Implementation
[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] Please see Figure 1 This invention provides a technical solution: an antibacterial, moisture-proof, and wear-resistant coating for air ducts and its preparation method. Addressing the technical shortcomings of existing air duct coatings, such as susceptibility to microbial growth in HVAC operating environments, easy hydrolysis failure in high humidity environments, and poor wear resistance under dusty airflow, this invention employs a double-layer composite coating structure design. Through the synergistic combination of electrochemical protection and physical shielding in the primer layer, and the hydrophobic and wear-resistant modification and multiple antibacterial and anti-mildew compounding of the functional topcoat layer, the overall protective performance and long-term service life of the air duct coating are effectively improved.
[0036] The coating of this invention has a double-layer composite structure, consisting of an inner primer layer that adheres to the duct substrate and an outer exposed functional topcoat layer. The two layers are tightly adhered and have complementary properties. The primer layer mainly serves to protect the substrate from corrosion, bond the interface, provide physical shielding, and offer electrochemical protection, while the functional topcoat layer mainly provides antibacterial, antifungal, hydrophobic, moisture-proof, erosion-resistant, abrasion-resistant, and aging-resistant protection.
[0037] Regarding specific thickness parameters, the dry film thickness of the primer layer is controlled at 25–35 μm, the dry film thickness of the functional topcoat layer is controlled at 45–65 μm, and the overall total dry film thickness of the coating is 70–100 μm. This thickness ratio ensures that the coating is lightweight and adaptable to the deformation of the duct substrate, while also taking into account the anti-corrosion protection effect of the underlying layer and the wear resistance and antibacterial properties of the top layer. It avoids the problems of protection failure due to excessively thin coating and cracking, peeling, and incomplete curing due to excessively thick coating.
[0038] The primer layer is formed by mixing and stirring primer component A and primer component B evenly, then coating and curing. The two components work together to achieve stable cross-linking and curing of the epoxy system, ensuring the adhesion and anti-corrosion performance of the primer layer.
[0039] By weight, the raw material ratio of primer component A is as follows: 15-20 parts water-based epoxy emulsion, 55-65 parts zinc powder, 5-10 parts ferrophosphorus powder, 0.5-1 part organobentonite, 2-4 parts co-solvent, and deionized water to make up to 100 parts. Among these, high-content zinc powder is the core raw material for sacrificial anode protection. Zinc powder with 800 mesh and a zinc content ≥97wt% can be uniformly dispersed within the coating, preferentially undergoing oxidation reaction when micro-corrosion points appear on the substrate, protecting the metal substrate of the duct. Ferrophosphorus powder possesses excellent physical shielding properties, filling coating pores and blocking water vapor and oxygen penetration, forming a synergistic anti-corrosion system with zinc powder. Organobentonite, as a rheology modifier, effectively improves the dispersion stability and anti-settling properties of the primer slurry, preventing metal powder agglomeration and stratification. The co-solvent assists the water-based epoxy emulsion in film formation, improving low-temperature film formation and coating density.
[0040] Component B of the primer is a water-based epoxy curing agent. Its dosage is determined based on the equivalent ratio of the epoxy equivalent of component A to the active hydrogen equivalent of component B, with the equivalent ratio controlled between 0.85 and 1.15, preferably between 0.9 and 1.1. This equivalent ratio range ensures sufficient cross-linking and curing of the epoxy resin, avoiding problems such as increased coating brittleness due to excessive curing agent and incomplete curing and decreased water resistance due to insufficient curing agent. The water-based epoxy emulsion selected in this invention has an epoxy equivalent of 450–550 g / eq and a solid content of 50 ± 2%, matched with a water-based epoxy curing agent with an active hydrogen equivalent of 250–300 g / eq, which can form a dense primer curing film with excellent adhesion.
[0041] In addition to the equivalent ratios of 0.9, 1.0, and 1.1 used in Examples 1-3 below, the ratios of epoxy equivalent to active hydrogen equivalent can also be 0.85 and 1.15 respectively for testing. The coating can still obtain acceptable overall performance, with only slight changes in coating brittleness or degree of curing, which can still meet the requirements for use in air ducts.
[0042] The functional topcoat layer is formed by mixing and curing topcoat component A and topcoat component B. It adopts an epoxy-polyurethane composite resin system, combined with inorganic wear-resistant modified powder, multiple antibacterial components and functional additives to achieve multiple performance integration.
[0043] By weight, the raw material ratio of component A of the topcoat is as follows: 28-36 parts of waterborne epoxy emulsion, 12-18 parts of waterborne polyurethane dispersion, 2-4 parts of nano-α-Al₂O₃ surface-modified with silane coupling agent, 1-2 parts of polytetrafluoroethylene micro powder, 3-5 parts of sericite powder, 0.5-1.2 parts of silver-zinc-glass carrier inorganic antibacterial agent, and 0.5-1.5 parts of polyhexamethylene guanidine hydrochloride (in a 20wt% aqueous solution). The following components are included: 0.3-0.8 parts of iodopropynyl butylcarbamate (based on 10wt% propylene glycol butyl ether solution), 0.3-0.8 parts of hydrophobic fumed silica, 0.3-0.8 parts of organobentonite, 2-4 parts of film-forming aid, 0.1-0.3 parts of defoamer, 0.1-0.3 parts of leveling agent, 0.2-0.5 parts of flash rust inhibitor, 0.2-0.5 parts of thickener, and deionized water to bring the total to 100 parts.
[0044] To further optimize the overall performance of the topcoat, based on the total resin solids content of the waterborne epoxy emulsion and waterborne polyurethane dispersion in component A of the topcoat, the preferred mass ratios of each functional powder and antibacterial component are as follows: nano α-Al₂O₃ 6–10 wt%, polytetrafluoroethylene micro powder 2–4 wt%, sericite powder 5–8 wt%, silver-zinc-glass carrier inorganic antibacterial agent 1.0–2.0 wt%, polyhexamethylene guanidine hydrochloride active ingredient 0.3–0.8 wt%, and iodopropynyl butylcarbamate active ingredient 0.3–0.5 wt%. This ratio range allows for synergistic effects of each functional component and avoids the coating performance imbalance caused by excessive amounts of a single component.
[0045] In the topcoat resin system, the waterborne epoxy emulsion provides coating hardness, adhesion and corrosion resistance, while the aliphatic polyester anionic waterborne polyurethane dispersion (solid content 35±2%, elongation at break ≥300%, glass transition temperature -30~-20℃) imparts high flexibility, impact resistance and low temperature aging resistance to the coating. The combination of the two can take into account both the rigidity and toughness of the coating, and is suitable for the airflow vibration conditions of the air duct.
[0046] In the wear-resistant and moisture-proof modified components, nano-α-Al2O3 with an average particle size of 50nm and a specific surface area ≥30m² / g, after being modified with a silane coupling agent, can be uniformly dispersed in the resin system, filling the micropores of the coating and improving the hardness and density of the coating; polytetrafluoroethylene micro powder with an average particle size of 3-5μm has extremely low surface energy, which can give the coating excellent hydrophobicity and self-lubricating properties, reducing airflow dust erosion and wear; sericite powder with a diameter-to-thickness ratio ≥40 can form a layered shielding structure, effectively blocking the penetration of water vapor and mold spores, and improving the moisture-proof and impermeable performance of the coating; hydrophobic fumed silica can further optimize the hydrophobic effect of the coating surface and inhibit the adsorption and accumulation of moisture.
[0047] The multiple antibacterial components employ an inorganic-organic compound system to achieve broad-spectrum and long-lasting antibacterial effects. Among them, the silver-zinc-glass carrier inorganic antibacterial agent (silver content 2-4wt%, zinc content 10-20wt%, D50≤5μm, carrier is borosilicate glass or zirconium phosphate) can slowly release metal ions, destroying the microbial cell membrane and enzyme system, thus achieving long-lasting antibacterial effects; polyhexamethylene guanidine hydrochloride with a molecular weight of 2000-5000Da can adsorb bacterial cells and inhibit microbial division and reproduction; iodopropynyl butylcarbamate can specifically inhibit mold growth. The three components work synergistically to comprehensively inhibit the reproduction of bacteria and mold in the duct environment and prevent biofilm formation.
[0048] Component B of the topcoat consists of a water-based epoxy curing agent and γ-glycidoxypropyltrimethoxysilane. The amount of γ-glycidoxypropyltrimethoxysilane is 1.5 to 2.5 wt% of the total mass of component A of the topcoat. It can act as an interfacial coupling agent and a crosslinking promoter. On the one hand, it improves the interfacial bonding force between inorganic powder and organic resin, preventing powder agglomeration and shedding. On the other hand, it participates in the epoxy crosslinking reaction, improving the stability of the coating structure. The amount of water-based epoxy curing agent is determined according to the ratio of epoxy equivalent of component A to active hydrogen equivalent of component B of the topcoat of 0.85 to 1.15 (preferably 0.9 to 1.1) to ensure that the topcoat layer is fully crosslinked and cured.
[0049] The preparation method of the above-mentioned antibacterial, moisture-proof and wear-resistant coating for air ducts of the present invention includes the following steps in sequence: nanopowder modification, preparation of topcoat component A, preparation of primer component A, substrate pretreatment, layered coating and stepped curing. The specific process parameters are as follows:
[0050] Nano-α-Al₂O₃ silane pretreatment: Nano-α-Al₂O₃ was uniformly dispersed in anhydrous ethanol to prepare a homogeneous suspension. Powder agglomeration was broken up using ultrasonic dispersion. Then, γ-glycidyl etheroxypropyltrimethoxysilane (3 wt% of the nano-α-Al₂O₃ mass) was added. The pH of the system was adjusted to 4–5 using acetic acid, and the reaction was carried out under constant temperature (50–70℃) with stirring for 2–6 hours. After the reaction, unreacted silane coupling agent was removed by centrifugation and repeated washing with anhydrous ethanol. After vacuum drying and fine grinding, modified nano-α-Al₂O₃ powder with complete surface modification and excellent dispersibility was obtained. This pretreatment process can graft organic functional groups onto the surface of nanopowders, improving their compatibility with epoxy and polyurethane resins, preventing powder precipitation and sedimentation, and ensuring the uniformity of coating performance.
[0051] Preparation of Topcoat Component A: Deionized water, organic bentonite, modified nano-α-Al2O3, polytetrafluoroethylene micropowder, sericite powder, silver-zinc-glass carrier inorganic antibacterial agent, and hydrophobic fumed silica were added sequentially to a mixing tank according to the specified ratio. After high-speed stirring and dispersion, the mixture was ground in a sand mill until the slurry fineness was ≤30μm, obtaining a uniform functional powder slurry. Subsequently, aqueous epoxy emulsion, aqueous polyurethane dispersion, polyhexamethylene guanidine hydrochloride aqueous solution, iodopropynyl butylcarbamate solution, film-forming aid, and flash rust inhibitor were added sequentially to the slurry, and mixed uniformly with low-speed stirring. Finally, defoamer, leveling agent, and thickener were added in batches to adjust the slurry viscosity to 60–90 s (Ford Cup 4). The mixture was then filtered to remove trace impurities and agglomerated particles, yielding topcoat component A. This preparation process ensures uniform dispersion of each functional component, avoids localized enrichment of additives, and guarantees the quality of the topcoat film.
[0052] Preparation of Primer Component A: Deionized water, organic bentonite, 800-mesh zinc powder, and ferrophosphorus powder are added to a grinding machine according to the specified ratio and ground until the fineness of the system is ≤30μm, ensuring that the metal powder is uniformly dispersed without agglomeration. Then, water-based epoxy emulsion and co-solvent are added, and after stirring and mixing evenly, a trace amount of defoamer is added to eliminate air bubbles in the system. The viscosity of the slurry is adjusted by continuous stirring until it reaches the 45-65s cup (Ford-4 cup). After filtration, primer component A is obtained. This process effectively avoids the sedimentation and stratification of zinc powder and ferrophosphorus powder, ensuring uniform and stable anti-corrosion performance of the primer.
[0053] Substrate pretreatment, coating and stepped curing: First, the metal substrate of the air duct is pretreated by degreasing to remove surface oil and roughening by sanding to improve the adhesion of the substrate. Then, silane treatment is performed by using 5wt% γ-glycidyl etheroxypropyltrimethoxysilane ethanol / water solution. Acetic acid is used to adjust the pH to 4-5. A 3-5μm wet film is formed by coating and drying at room temperature for 10-15 minutes. The primer coating must be completed within 24 hours to avoid secondary oxidation and contamination of the substrate.
[0054] The prepared primer components A and B are mixed evenly in equal proportions and applied to the pretreated duct substrate surface by spraying or brushing to form a 40-60 μm wet film. The film is then pre-baked at 60-80℃ for 5-10 minutes until touch-dry, resulting in a uniform and dense primer layer. Within 24 hours of the primer layer being surface dry, topcoat components A and B are mixed evenly and applied to form an 80-120 μm wet film.
[0055] After the topcoat is applied, a stepped curing process is used to complete the overall curing. The specific process is as follows: First, curing is carried out at a low temperature of 50–70℃ for 20–40 minutes to allow the coating surface to initially form a film and set, avoiding pinholes and bubbles caused by rapid high-temperature curing; then, the temperature is increased to 70–90℃ for medium-temperature curing for 20–40 minutes to promote full cross-linking of the resin and tight bonding between the powder and resin interface; finally, it is allowed to cool naturally to room temperature and left to cure completely for 24 hours, resulting in the finished composite coating. This stepped curing process allows for a gradual cross-linking reaction of the coating, effectively avoiding problems such as coating cracking, peeling, and incomplete curing, significantly improving the structural stability and mechanical properties of the coating.
[0056] Specific embodiments, comparative examples, and performance tests
[0057] Examples 1-3 in this section all fall within the parameter range defined by the claims; Comparative Examples 1-3 omit some key technical features of the present invention. The raw material grades and specifications used in each example and comparative example are kept consistent, with only the component dosages or process conditions adjusted.
[0058] Coating sample testing was conducted in accordance with current national standards:
[0059] Cross-cut adhesion: GB / T 9286-2021;
[0060] Neutral salt spray test: GB / T 10125-2021;
[0061] Abrasion test (sand drop method): GB / T 23988-2009; the sand drop medium is standard quartz sand, the sand drop height is 1000mm, and the volume of sand consumed per unit thickness of wear is recorded; the larger the value of the sand drop abrasion loss, the better the abrasion resistance of the coating.
[0062] Antibacterial rate test (Escherichia coli): GB / T 31402-2015;
[0063] Mildew resistance rating: GB / T 1741-2020;
[0064] Water resistance: GB / T 1733-1993 Method A, immerse in deionized water at 23±2℃ for 240h, remove and air dry, and observe the coating for blistering and peeling.
[0065] Example 1
[0066] Primer component A (parts by weight): 17 parts waterborne epoxy emulsion, 60 parts zinc powder, 7 parts phosphate iron powder, 0.7 parts organic bentonite, 3 parts co-solvent, and deionized water to make up to 100 parts;
[0067] Primer component B: water-based epoxy curing agent, epoxy equivalent / active hydrogen equivalent = 1.0;
[0068] Primer dry film thickness: 30μm.
[0069] Topcoat Component A (parts by weight): 32 parts waterborne epoxy emulsion, 15 parts waterborne polyurethane dispersion, 3 parts silane-modified nano α-Al2O3, 1.5 parts polytetrafluoroethylene micro powder, 4 parts sericite powder, 0.8 parts silver-zinc-glass carrier inorganic antibacterial agent, 1.0 part polyhexamethylene guanidine hydrochloride (20wt% aqueous solution), 0.5 parts iodopropynyl butylcarbamate (10wt% propylene glycol butyl ether solution), 0.5 parts hydrophobic fumed silica, 0.5 parts organic bentonite, 3 parts film-forming aid, 0.2 parts defoamer, 0.2 parts leveling agent, 0.3 parts anti-flash rust agent, 0.3 parts thickener, deionized water to 100 parts;
[0070] Topcoat Component B: Water-based epoxy curing agent (epoxy equivalent / active hydrogen equivalent = 1.0), γ-glycidyl etheroxypropyltrimethoxysilane accounts for 2.0 wt% of the total mass of topcoat A;
[0071] Topcoat dry film thickness: 55μm; Total dry film thickness: 85μm.
[0072] Preparation process:
[0073] Nano-α-Al2O3 silane modification: reaction temperature 60℃, reaction time 4h;
[0074] Topcoat A viscosity: Fore-4 cup 75s; Primer A viscosity: Fore-4 cup 55s;
[0075] Substrate silane pretreatment wet film 4μm; primer wet film 50μm, pre-baked at 70℃ for 8min until touch dry; topcoat wet film 100μm;
[0076] Step curing: Hold at 60℃ for 30 min, then at 80℃ for 30 min, and allow to stand at room temperature for 24 h for complete curing.
[0077] Example 2
[0078] Primer component A (parts by weight): 15 parts waterborne epoxy emulsion, 55 parts zinc powder, 5 parts phosphate iron powder, 0.5 parts organic bentonite, 2 parts co-solvent, and deionized water to make up to 100 parts.
[0079] Primer component B: water-based epoxy curing agent, epoxy equivalent / active hydrogen equivalent = 0.9;
[0080] Primer dry film thickness: 25μm.
[0081] Topcoat Component A (parts by weight): 28 parts waterborne epoxy emulsion, 12 parts waterborne polyurethane dispersion, 2 parts silane-modified nano α-Al2O3, 1 part polytetrafluoroethylene micro powder, 3 parts sericite powder, 0.5 parts silver-zinc-glass carrier inorganic antibacterial agent, 0.5 parts polyhexamethylene guanidine hydrochloride (20wt% aqueous solution), 0.3 parts iodopropynyl butylcarbamate (10wt% propylene glycol butyl ether solution), 0.3 parts hydrophobic fumed silica, 0.3 parts organic bentonite, 2 parts film-forming aid, 0.1 parts defoamer, 0.1 parts leveling agent, 0.2 parts anti-flash rust agent, 0.2 parts thickener, deionized water to 100 parts;
[0082] Topcoat Component B: Water-based epoxy curing agent (epoxy equivalent / active hydrogen equivalent = 0.9), γ-glycidyl etheroxypropyltrimethoxysilane accounts for 1.5 wt% of the total mass of topcoat A;
[0083] Topcoat dry film thickness: 45μm; Total dry film thickness: 70μm.
[0084] Preparation process:
[0085] Nano-α-Al₂O₃ silane modification: reaction temperature 50℃, reaction time 2h;
[0086] Topcoat A viscosity: Fore-4 cup 60s; Primer A viscosity: Fore-4 cup 45s;
[0087] Substrate silane pretreatment wet film 3μm; primer wet film 40μm, pre-baked at 60℃ for 5min until touch dry; topcoat wet film 80μm;
[0088] Step curing: Hold at 50℃ for 20 min, then at 70℃ for 20 min, and allow to stand at room temperature for 24 h for complete curing.
[0089] Example 3
[0090] Primer component A (parts by weight): 20 parts waterborne epoxy emulsion, 65 parts zinc powder, 10 parts phosphate iron powder, 1 part organic bentonite, 4 parts co-solvent, and deionized water to make up to 100 parts.
[0091] Primer component B: water-based epoxy curing agent, epoxy equivalent / active hydrogen equivalent = 1.1;
[0092] Primer dry film thickness: 35μm.
[0093] Topcoat Component A (parts by weight): 36 parts waterborne epoxy emulsion, 18 parts waterborne polyurethane dispersion, 4 parts silane-modified nano α-Al2O3, 2 parts polytetrafluoroethylene micro powder, 5 parts sericite powder, 1.2 parts silver-zinc-glass carrier inorganic antibacterial agent, 1.5 parts polyhexamethylene guanidine hydrochloride (20wt% aqueous solution), 0.8 parts iodopropynyl butylcarbamate (10wt% propylene glycol butyl ether solution), 0.8 parts hydrophobic fumed silica, 0.8 parts organic bentonite, 4 parts film-forming aid, 0.3 parts defoamer, 0.3 parts leveling agent, 0.5 parts anti-flash rust agent, 0.5 parts thickener, deionized water to make up to 100 parts;
[0094] Topcoat Component B: Water-based epoxy curing agent (epoxy equivalent / active hydrogen equivalent = 1.1), γ-glycidyl etheroxypropyltrimethoxysilane accounts for 2.5 wt% of the total mass of topcoat A;
[0095] Topcoat dry film thickness: 65μm; total dry film thickness: 100μm.
[0096] Preparation process:
[0097] Nano-α-Al2O3 silane modification: reaction temperature 70℃, reaction time 6h;
[0098] Topcoat A viscosity: Fore-4 cup 90s; Primer A viscosity: Fore-4 cup 65s;
[0099] Substrate silane pretreatment wet film 5μm; primer wet film 60μm, pre-baked at 80℃ for 10min until touch dry; topcoat wet film 120μm;
[0100] Step curing: Hold at 70℃ for 40 min, then at 90℃ for 40 min, and allow to stand at room temperature for 24 h for complete curing.
[0101] Comparative Example 1
[0102] The results are largely consistent with Example 1; the difference is that γ-glycidoxypropyltrimethoxysilane is not added to component B of the topcoat. This is used to investigate the effect of the lack of interfacial coupling-crosslinking promoting components in the topcoat system on coating density, interlayer adhesion, and moisture resistance.
[0103] Comparative Example 2
[0104] The results are largely consistent with Example 1; the difference lies in that only the silver-zinc-glass carrier inorganic antibacterial agent is retained in component A of the topcoat, while polyhexamethylene guanidine hydrochloride and iodopropynyl butylcarbamate are removed. This is used to examine the difference in antibacterial and antifungal effects of a single inorganic antibacterial system without the presence of organic antibacterial and antifungal components.
[0105] Comparative Example 3
[0106] The process is largely consistent with Example 1; the difference is that the stepped curing process is omitted, and the topcoat is directly cured at 80°C for 60 minutes after application. This is used to investigate the impact of the change in curing process on the appearance, internal defects, and overall mechanical properties of the coating.
[0107] Table 1. Coating performance test results for each embodiment and comparative example:
[0108] Cross-grain adhesion / grade 0 1 0 2 0 1 neutral salt spray / h 720 600 720 480 720 540 Abrasion loss due to sand falling / (L / μm) 125 142 118 153 127 164 E. coli antibacterial rate / % 99.6 99.1 99.7 99.4 93.2 99.2 Anti-mildew rating Level 0 Level 1 Level 0 Level 1 Level 3 Level 1 Water resistance 240h condition No bubbling, no peeling No bubbling, no peeling No bubbling, no peeling Localized blistering No bubbling A small number of pinholes
[0109] As can be seen from the test results in Table 1:
[0110] Examples 1-3, due to the use of the component ratio and preparation process specified in this invention, have coatings with good adhesion, salt spray corrosion resistance, and low wear loss. At the same time, their antibacterial, anti-mildew, and water-resistant properties are suitable for use in ductwork under conditions of high humidity, dust, and easy growth of microorganisms.
[0111] In Comparative Example 1, without the introduction of γ-glycidoxypropyltrimethoxysilane into component B of the topcoat, the interfacial bonding effect of the coating decreased, the interlayer adhesion deteriorated, the salt spray duration decreased, and local blistering appeared in the water resistance test. This indicates that the silane component plays a role in improving the inorganic-organic interface and enhancing the moisture-proof and corrosion-proof performance of the coating.
[0112] Comparative Example 2 used only inorganic antibacterial agents, lacking the combination of polyhexamethylene guanidine hydrochloride and iodopropynyl butylcarbamate. The antibacterial rate of Escherichia coli was reduced and the antifungal level was significantly worse. This indicates that only by working together can the inorganic-organic compound antibacterial and antifungal components achieve simultaneous inhibition of bacteria and mold.
[0113] Comparative Example 3 eliminated the stepped curing process and adopted a single high-temperature curing process. The coating was prone to pinhole defects, resulting in a decrease in wear resistance. This proves that the stepped curing process can reduce coating defects and improve the mechanical protection performance of the coating.
[0114] The above test results show that the various technical features of the present invention do not work in isolation. The component ratio, the selection of functional additives, and the preparation process work together to obtain a duct coating that has antibacterial, moisture-proof, wear-resistant, and corrosion-resistant properties.
[0115] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An antibacterial, moisture-proof, and wear-resistant coating for air ducts, comprising a primer layer and a functional topcoat layer sequentially disposed on the surface of an air duct substrate, characterized in that: The primer layer is formed by mixing primer component A and primer component B and then coating and curing. Primer component A includes, by mass, 15-20 parts of water-based epoxy emulsion, 55-65 parts of zinc powder, 5-10 parts of phosphorus iron powder, 0.5-1 parts of organic bentonite, 2-4 parts of co-solvent, and deionized water to make up to 100 parts. The primer component B is a water-based epoxy curing agent, and its dosage is determined by calculating the equivalent of epoxy in primer component A and active hydrogen in primer component B. The functional topcoat layer is formed by mixing and coating topcoat component A and topcoat component B, and then curing. Topcoat component A, by weight, comprises: 28-36 parts of waterborne epoxy emulsion, 12-18 parts of waterborne polyurethane dispersion, 2-4 parts of nano-α-Al₂O₃ surface-modified with silane coupling agent, 1-2 parts of polytetrafluoroethylene micropowder, 3-5 parts of sericite powder, 0.5-1.2 parts of silver-zinc-glass carrier inorganic antibacterial agent, and 0.5-1.2 parts of polyhexamethylene guanidine hydrochloride. 1.5 parts (based on a 20 wt% aqueous solution), 0.3-0.8 parts (based on a 10 wt% propylene glycol butyl ether solution), 0.3-0.8 parts hydrophobic fumed silica, 0.3-0.8 parts organobentonite, 2-4 parts film-forming aid, 0.1-0.3 parts defoamer, 0.1-0.3 parts leveling agent, 0.2-0.5 parts flash rust inhibitor, 0.2-0.5 parts thickener, and deionized water to bring the total to 100 parts; The topcoat component B is composed of an aqueous epoxy curing agent and γ-glycidoxypropyltrimethoxysilane. The amount of γ-glycidoxypropyltrimethoxysilane is 1.5 to 2.5 wt% of the total mass of the topcoat component A. The amount of the aqueous epoxy curing agent is determined by calculation based on the equivalent of epoxy in the topcoat component A and the equivalent of active hydrogen in the topcoat component B. The dry film thickness of the primer layer is 25–35 μm, the dry film thickness of the functional topcoat layer is 45–65 μm, and the total dry film thickness of the coating is 70–100 μm.
2. The antibacterial, moisture-proof, and wear-resistant coating for air ducts according to claim 1, characterized in that: In the functional topcoat layer, based on the total resin solids content of the aqueous epoxy emulsion and aqueous polyurethane dispersion in component A of the topcoat, the content of each component is as follows: Nano α-Al₂O₃ 6~10wt%; 2-4 wt% polytetrafluoroethylene micro powder; 5-8 wt% sericite powder; Silver-zinc-glass carrier inorganic antibacterial agent 1.0–2.0 wt%; Polyhexamethylene guanidine hydrochloride, 0.3–0.8 wt% based on active ingredient; Iodopropynyl butylcarbamate, 0.3-0.5 wt% based on active ingredient.
3. The antibacterial, moisture-proof, and wear-resistant coating for air ducts according to claim 1, characterized in that: The amount of waterborne epoxy curing agent in the primer B component and / or the topcoat B component is determined according to the ratio of epoxy equivalent in the primer A component or the topcoat A component to active hydrogen equivalent in the primer B component or the topcoat B component, which is 0.85 to 1.15; preferably 0.9 to 1.1; the γ-glycidoxypropyltrimethoxysilane in the topcoat B component is used as an interfacial coupling agent and a crosslinking promoter.
4. The antibacterial, moisture-proof, and wear-resistant coating for air ducts according to claim 1, characterized in that: The nano-α-Al2O3 modified with silane coupling agent has an average particle size of 50 nm and a specific surface area of ≥30 m² / g. The silane coupling agent used is γ-glycidoxypropyltrimethoxysilane, and its amount is 3 wt% of the mass of nano-α-Al2O3.
5. The antibacterial, moisture-proof, and wear-resistant coating for air ducts according to claim 1, characterized in that: The silver-zinc-glass carrier inorganic antibacterial agent has a silver content of 2-4 wt%, a zinc content of 10-20 wt%, and a median particle size D50 ≤ 5 μm. The carrier is borosilicate glass or zirconium phosphate. The polyhexamethylene guanidine hydrochloride has a molecular weight of 2000-5000 Da.
6. The antibacterial, moisture-proof, and wear-resistant coating for air ducts according to claim 1, characterized in that: The aqueous epoxy emulsion has an epoxy equivalent of 450–550 g / eq and a solid content of 50 ± 2%; the aqueous epoxy curing agent has an active hydrogen equivalent of 250–300 g / eq; the aqueous polyurethane dispersion is an aliphatic polyester anionic dispersion with a solid content of 35 ± 2%, an elongation at break ≥ 300%, and a glass transition temperature of -30 to -20℃.
7. The antibacterial, moisture-proof, and wear-resistant coating for air ducts according to claim 1, characterized in that: The sericite powder has an aspect ratio ≥40; the polytetrafluoroethylene micro powder has an average particle size of 3-5 μm; the zinc powder has a mesh size of 800 mesh and a zinc content ≥97 wt%.
8. A method for preparing an antibacterial, moisture-proof, and wear-resistant coating for air ducts as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1, silane pretreatment of nano α-Al2O3: Nano α-Al2O3 is dispersed in anhydrous ethanol to form a suspension. After ultrasonic dispersion, γ-glycidoxypropyltrimethoxysilane is added, the pH is adjusted to 4-5, and the reaction is stirred at 50-70℃ for 2-6 hours. After separation, washing, drying and grinding, nano α-Al2O3 modified with silane coupling agent is obtained. Step 2, Preparation of Topcoat Component A: Deionized water, organic bentonite, nano α-Al2O3 obtained in Step 1, polytetrafluoroethylene micro powder, sericite powder, silver-zinc-glass carrier inorganic antibacterial agent, and hydrophobic fumed silica are mixed, dispersed, and ground to a fineness ≤30μm to obtain a slurry; waterborne epoxy emulsion, waterborne polyurethane dispersion, polyhexamethylene guanidine hydrochloride aqueous solution, iodopropynyl butylcarbamate solution, film-forming aid, and anti-flash rust agent are added to the slurry and mixed evenly; then defoamer, leveling agent, and thickener are added to adjust the viscosity to 60-90s at Forck-4 cup, and the mixture is filtered to obtain topcoat component A; Step 3, Preparation of primer component A: Mix and grind deionized water, organic bentonite, zinc powder and iron phosphate powder to a fineness of ≤30μm, then add water-based epoxy emulsion, cosolvent and defoamer and mix evenly, adjust the viscosity to 45-65s of Forecast cup 4, and filter to obtain primer component A; Step 4, Coating and Curing: After degreasing, sanding, and silane pretreatment of the duct substrate, primer component A and primer component B are mixed and coated to form a wet film of 40-60 μm. The film is then pre-baked at 60-80℃ for 5-10 minutes until touch-dry to obtain a primer layer. Within 24 hours after the primer layer is surface-dry, topcoat component A and topcoat component B are mixed and coated to form a wet film of 80-120 μm. This film is then cured in stages to obtain the antibacterial, moisture-proof, and wear-resistant coating for the duct. The amount of water-based epoxy curing agent in primer component B and / or topcoat component B is determined according to the ratio of epoxy equivalent in primer component A or topcoat component A to active hydrogen equivalent in primer component B or topcoat component B, which is 0.85-1.15; preferably 0.9-1.
1.
9. The preparation method according to claim 8, characterized in that: The silane pretreatment in step four uses a 5 wt% ethanol / water solution of γ-glycidoxypropyltrimethoxysilane, adjusts the pH to 4-5 with acetic acid, achieves a wet film thickness of 3-5 μm, dries at room temperature for 10-15 min, and completes the primer coating within 24 h.
10. The preparation method according to claim 8, characterized in that: The step-curing process described in step four is as follows: first, cure at 50-70℃ for 20-40 minutes, then raise the temperature to 70-90℃ and cure for 20-40 minutes, then allow to cool naturally and leave at room temperature for 24 hours to complete the curing process.